Pemanfaatan Lean Production untuk Perbaikan Kinerja Sistem Manufaktur pada Perusahaan Tas PT TIJ - Iveline Anne Marie; Emelia Sari; Didien Suhardini; Fani Puspitasari; Tono Sukarnoto; Auliya Dewi Oktriana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
The implementation of this Community Service program is part of the activities of the Production Systems Laboratory of the Industrial Engineering Department, FTI Trisakti University, as an effort to share knowledge in industrial society. PT TIJ is a women's bag company located on Jl. Raya Bogor km.38 No.1 Cilodong - Depok. grow with family management. Companies need knowledge sharing in order to increase efficiency and company performance for plans to increase bag production capacity. Community service activities in the form of counseling and mentoring activities to industrial community, namely employees of the PT TIJ bag company. Based on interviews and observations, it can be seen that there are inefficiency problems in production process activities, plans to increase production capacity and the need for finished product warehouse layout design..Counseling activities are carried out using zoom media followed by visits to companies to provide consultations in the context of assisting companies to understand the utilization of Industrial Engineering knowledge, namely Lean Production to improve company performance. PkM activities at PT TIJ with the topic of Utilizing Lean Production include material: Lean Production Systems, Facility Layout Design, Time Study and Movement Study as well as Machine Maintenance material which has been carried out well, it is hoped that this can reduce the inefficiencies that occur thereby improving the performance of the company's manufacturing system.